Joint Modeling of Immune Reconstitution Post Haploidentical Stem Cell Transplantation in Pediatric Patients With Acute Leukemia Comparing CD34+-Selected to CD3/CD19-Depleted Grafts in a Retrospective Multicenter Study - Salzmann-Manrique, Emilia; Bremm, Melanie; Huenecke, Sabine; Stech, Milena; Orth, Andreas; Eyrich, Matthias; Schulz, Ansgar; Esser, Ruth; Klingebiel, Thomas; Bader, Peter; Herrmann, Eva; Koehl, Ulrike (Frontiers in Immunology, 2018)
Rapid immune reconstitution following stem cell transplantation (SCT) is essential for a favorable outcome. The optimization of graft composition should not only enable a sufficient immune reconstitution but also improve graft versus leukemia/tumor effects, overcome infectious complications and, finally, improve patient survival. Especially in haploidentical SCT, the optimization of graft composition is controversial. Therefore, we analyzed the influence of graft manipulation on immune reconstitution in 40 patients with acute leukemia in remission. We examined the cell recovery post haploidentical SCT in patients receiving a CD34+-selected or CD3/CD19-depleted graft, considering the applied conditioning regimen. We used joint model analysis for overall survival and analyzed the dynamics of age-adjusted leukocytes; lymphocytes; monocytes; CD3+, CD3+CD4+ and CD3+CD8+ T-cells; natural killer (NK) cells; and B-cells over the course of time after SCT. Lymphocytes, NK cells and B-cells expanded more rapidly after SCT with CD34+-selected grafts (P=0.036, P=0.002, and P<0.001, respectively). Contrarily, CD3+CD4+ helper T-cells recovered delayer in the CD34 selected group (P=0.026). Furthermore, reduced intensity conditioning facilitated faster immune recovery of lymphocytes and T-cells and their subsets (P<0.001). However, the immune recovery for NK cells and B-cells was comparable for patients who received reduced-intensity or full preparative regimens Dynamics of all cell types had a significant influence on overall survival, which did not differ between patients receiving CD34+-selected and those receiving CD3/CD19-depleted grafts. In conclusion, cell reconstitution dynamics showed complex diversity with regard to the graft manufacturing procedure and conditioning regimen.